2008
DOI: 10.1530/rep-07-0507
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal effects on the response of ovarian follicles to IGF1 in mares

Abstract: The response of follicles to IGF1 was compared between the transition into the ovulatory season (transitional period) and the ovulatory season (ovulatory period) in eight mares using a cross-over experimental design within periods. Granulosa cells were collected from follicles 15-24 or 25-34 mm and expression of IGF1R, IGF2R, FSHR, LHCGR and PAPPA was determined by qPCR. In addition, 10 mg IGF1 or vehicle were injected into the largest follicle (transitional period) or the second largest follicle (ovulatory pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Follicular aspiration was performed by trans-vaginal ultrasound-guided follicle puncture using a 17 gauge, 55 cm long ovum pickup needle (Popper & Sons, Inc., New Hyde Park, NY, USA) and an Aloka 500V ultrasound scanner (BCF Technology, Rochester, MN, USA) equipped with a 5 mHz curved array transducer, as described in Doyle et al (2008). Antral fluid was completely aspirated from each follicle and aspirates were centrifuged at 700 g for 10 min to separate granulosa cell pellets from fluid supernatant.…”
Section: Experimental Animals and General Proceduresmentioning
confidence: 99%
“…Follicular aspiration was performed by trans-vaginal ultrasound-guided follicle puncture using a 17 gauge, 55 cm long ovum pickup needle (Popper & Sons, Inc., New Hyde Park, NY, USA) and an Aloka 500V ultrasound scanner (BCF Technology, Rochester, MN, USA) equipped with a 5 mHz curved array transducer, as described in Doyle et al (2008). Antral fluid was completely aspirated from each follicle and aspirates were centrifuged at 700 g for 10 min to separate granulosa cell pellets from fluid supernatant.…”
Section: Experimental Animals and General Proceduresmentioning
confidence: 99%
“…Other studies reported no relationship between the granulosa IGF1R mRNA expression and follicle development in cattle (Armstrong et al, 2000), sheep (Hastie & Haresign, 2006), and pigs (Liu et al, 2000). In this regard, it is worth noting that mRNA expression may not precisely reflect the actual abundance of the functional protein (Doyle et al, 2008); therefore, more in‐depth studies are required to characterize the functional IGF1R protein in the follicle wall in relation to follicle development.…”
Section: Discussionmentioning
confidence: 99%
“…In mares fed with a low energy diet or protein during the winter, Sticker et al (1995a) observed diminished IGF-1 secretion, an important factor for follicular development. In mares, IGF-1 and its receptors increase specifically in the dominant follicle before divergence (Doyle et al 2008), making it possible to attribute a special role to IGF-1 in the selection and subsequent development of ovulatory follicles (Ginther et al 2004).…”
Section: Figmentioning
confidence: 99%